2014
DOI: 10.5455/msm.2014.26.211-215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipoic Acid on Acrylamide Induced Testicular Damage

Abstract: Introduction: Acrylamide is very toxic to various organs and associated with significant increase of oxidative stress and depletion of antioxidants. Alpha-lipoic acid enhances cellular antioxidant defense capacity, thereby protecting cells from oxidative stress. Aim of the study: This study aimed to evaluate the protective role of alpha-lipoic acid on the oxidative damage induced by acrylamide in testicular and epididymal tissues. Material and methods: Forty adult male rats were divided into four groups (10 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…; Lebda et al . ). The antioxidant activities of phenolics‐like quercetin are related to a number of different mechanisms, such as free radical‐scavenging, hydrogen‐donation (Tátraaljai et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…; Lebda et al . ). The antioxidant activities of phenolics‐like quercetin are related to a number of different mechanisms, such as free radical‐scavenging, hydrogen‐donation (Tátraaljai et al .…”
Section: Resultsmentioning
confidence: 97%
“…The present results were in agreement with Tyl and Friedman () and Lebda et al . () who showed that ACR lowered testosterone hormone levels, alters sperm motility and induces testicular atrophy. However, the treatment with quercetin led to noticed decrease of testosterone levels (Table ).Oxidative stress markers (8‐hydroxy deoxyguanosine, PC and LPO levels) were determined in the rat tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that 'these findings for the first time demonstrate that the neuromodulatory propensity of geraniol is indeed comparable to that of curcumin and may be exploited as a therapeutic adjuvant in the management of varied human neuropathy conditions'. Lebda et al (2014) Effects of lipoic acid on AA induced testicular damage…”
Section: Muralidhara (2014)mentioning
confidence: 99%